CONVERGENCE OR DIVERGENCE OF REGIONS OF MIDDLE-EAST EUROPE AFTER THEIR ACCESSION TO THE EUROPEAN UNION - Górna, Joanna Maria; Górna, Karolina Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The work presents the analysis of per capita GDP in the selected area of eight European countries (the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia and Slovenia) in two periods: 2000-2004 and 2005-2011, i.e. before and after their accession to the European Union. It was expected that accession to the EU would improve living conditions and would raise the pace of steady economic growth rate in those countries. It would enable the diminution of differences of income levels in the countries. The aim of the analysis is to investigate whether the phenomena of convergence or divergence of per capita GDP across the established regions according to the European classification system NUTS-2 have occurred in the periods considered. In the investigation some methods and models offered by the spatial statistics and econometrics will be used. Choosing the methodology was motivated by the hypothesis that the growth rate of any region is connected with the growth rates of its neighbors. Thus, the conception of economic convergence of the regions of the established area in the context of spatial connections is analyzed. The spatial trends and spatial autocorrelation of the GDP are considered. The changes in time of the spatial tendencies and dependence are analyzed as well. The main tools used in the investigation are the spatial cross-sectional data models and the spatial panel models of β-convergence. The data related to the established regions was taken from the database released by Eurostat (http://epp.eurostat.ec.europa.eu/).